Generalized rational $ α_{*}- $ contraction in $ C^{*}- $algebra-valued b-metric spaces - Rossafi, Mohamed; Massit, Hafida; Kari, Abdelkarim (Jurnal Matematika, Statistika dan Komputasi, 2022)
This present paper extends some common fixed point theorems for generalized rational $ α_{*}- $ contraction of multi-valued mappings in the setting of $ C^{*}- $algebra-valued b-metric spaces .